An Indoor Environmental Quality (IEQ) assessment of a partially-retrofitted university building. (July 2018) - Zuhaib, Sheikh; Manton, Richard; Griffin, Corey; Hajdukiewicz, Magdalena; Keane, Marcus M.; Goggins, Jamie
Abstract: Achieving standards-based Indoor Environmental Quality (IEQ) in existing buildings is growing steadily due to the strong demand for deep retrofits in Europe. Existing non-domestic buildings pose challenges mainly due to occupancy patterns, lack of personal control over comfort and outdated building structures. Renovations of many post-war non-domestic buildings (>35 years old) have faced technical and financial challenges. Consequently, these buildings are often only partially retrofitted, which are often ad-hoc in nature. This paper describes the evaluation process of indoor environmental conditions in a partially-retrofitted university building in Galway (Ireland) originally built during the 1970s and partially retrofit in 2005. The research assesses criteria outlined in EN 15251 and draws on methods from ASHRAE 55 and CBE IEQ survey. Occupant surveys complemented by physical measurements were used to assess the compliance of IEQ parameters for thermal, visual and acoustic comfort and indoor air quality. The relationship between the performance of the building envelope and occupant comfort is described across retrofitted and non-retrofitted zones of the building. The results suggest that ad-hoc retrofitting of the façade did not make any significant difference to IEQ and occupants continued to adapt personally to the existing conditions. Their preferred satisfaction levels in the survey were lower than the measured thermal sensation. It is recommended that future retrofits are adequately planned and optimised to improve both IEQ and energy performance. A whole building retrofit approach must balance and include factors such as human health, building fabric and energy savings to avoid the pitfalls of current practice. Highlights: Indoor Environmental Quality assessment of a partially-retrofitted building. Method based on standards EN 15251, ASHRAE 55, and Occupant IEQ Survey. Determined occupants' acceptable thermal, visual and acoustic comfort and IAQ ranges. Ad-hoc partial retrofit did not improve IEQ, occupants adapted to discomfort. Retrofits should be planned and optimised for IEQ and energy performance.